Bioevaluation of synthetic pyridones as dual inhibitors of α‐amylase and α‐glucosidase enzymes and potential antioxidants. Issue 1 (25th October 2022) - Saleem, Faiza; Khan, Khalid Mohammed; Ullah, Nisar; Özil, Musa; Baltaş, Nimet; Hameed, Shehryar; Salar, Uzma; Wadood, Abdul; Rehman, Ashfaq Ur; Kumar, Mukesh; Taha, Muhammad; Haider, Syed Moazzam
Abstract: Herein, a library of novel pyridone derivatives 1–34 was designed, synthesized, and evaluated for α‐amylase and α‐glucosidase inhibitory as well as antioxidant activities. Pyridone derivatives 1–34 were synthesized via a one‐pot multi‐component reaction of variously substituted aromatic aldehydes, acetophenone, ethyl cyanoacetate, and ammonium acetate in absolute ethanol. Synthetic compounds 1–34 were structurally characterized by different spectroscopic techniques. Most of the tested compounds showed more promising inhibition potential than the standard acarbose (IC50  = 14.87 ± 0.16 µM) but compounds 13 and 12 were found to be the most potent compounds with IC50 values of 9.20 ± 0.14 µM and 3.05 ± 0.18 µM against α‐amylase and α‐glucosidase enzymes, respectively. Compounds 1–34 also displayed moderate antioxidant potential in the range of IC50  = 96.50 ± 0.45 to 189.98 ± 1.00 µM in comparison to the control butylated hydroxytoluene (BHT) (IC50  = 66.50 ± 0.36 µM), in DPPH radical scavenging activities. Additionally, all synthetic derivatives were subjected to a molecular docking study to investigate the interaction details of compounds 1–34 (ligands) with the active site of enzymes (receptors). These results indicate that the newly synthesized pyridone class may serve as promising lead candidates for controlling diabetes mellitus and as antioxidants. Abstract : A library of novel pyridone derivatives (1–34 ) was designed, synthesized, and evaluated for α‐amylase and α‐glucosidase inhibitory as well as antioxidant activities. Most of the tested compounds showed more promising inhibition potential than the standard acarbose. All derivatives were subjected to a molecular docking study to investigate their interaction with the active site of the enzymes.